PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN RESTORAN XYZ - Andres Dharma Nurhalim (Jurnal Bina Manajemen, 2019)
The purpose of the research in this thesis is to analyze the influence of leadership style, job satisfaction and motivation on employee performance at XYZ restaurants. The analytical method used by the author in conducting this research is to use quantitative research with a population of 83 respondents who are XYZ restaurant employees. In carrying out the data collection, it was carried out by distributing questionnaires in which there were several statements. in this study the variables are divided into several parts including leadership style (X1), job satisfaction (X2) and motivation (X3) as independent variables, and employee performance (Y) as the dependent variable. To measure the magnitude of the influence on these variables, the authors use the method of linear regression and multiple regression analysis. From the results of the analysis it was found that there were significant and simultaneous effects on the variables of leadership style, job satisfaction and motivation on employee performance at XYZ restaurants